Lack of Nutritional Intake in Women Increases the Risk of Menstrual Disorders in Agricultural Areas - Zalsabilla, Adhelia Reisa; Safitri, Andini Eka; Putri, Jovanka Maylafaisya; Kurniyawan, Enggal Hadi; Kurniawan, Dicky Endrian; Nur, Kholid Rosyidi Muhammad; Afandi, Alfid Tri (Jurnal Bidan Mandiri, 2024)
Introduction: Nutritional intake is crucial in maintaining overall health, particularly women's reproductive health. Inadequate nutrition can lead to various menstrual disorders, such as menstrual pain, anemia, and amenorrhea. Addressing these issues is vital for improving women's health. Objectives: To examine the impact of inadequate nutrition on menstrual health, identify critical nutritional deficiencies contributing to menstrual disorders, and suggest potential interventions to improve women's reproductive health and overall well-being in agricultural areas. Methods: This study uses the PRISMA method to review 9.913 articles in total with the following details: 8,900 articles found on Google Scholar, 896 articles on Pubmed, and 7.292 articles on ScienceDirect. Ten relevant ones highlighted the significant impact of inadequate nutrition on menstrual health among women in agricultural areas. Results: Inadequate nutritional intake significantly impacts menstrual health, leading to disorders such as amenorrhea and anemia among women in agricultural areas, emphasizing the need for improved nutrition and food security in this population. Conclusion: The review of the studies shows that poor nutrition and harsh working conditions in agricultural areas lead to menstrual disorders, highlighting the need for improved nutrition, education, and working conditions to enhance women's reproductive health and overall well-being